A catalogue of some Musa ITC reference collections grown in the Philippines - Gueco, Leon S.; Corpuz, F.V.; Silvestre, O.O.; Silva, F.F.M.; Cueva, F.M. de la; Regner, A.I.; Fabregar, E.G.; Sinohin, V.G.O.; Molina, A.B. (2017)
The catalogue includes 25 ITC Musa accessions from different subgroups characterized using the minimum set of morphological descriptors and photos. Supplemental information on the disease reaction of the accessions against Fusarium Wilt (Foc TR4) and Banana Bunchy Top Virus were also included. The completion of this catalogue was made possible by Bioversity International for developing and implementing the project entitled “Assessment of Musa Genetic Resources for their Host Reaction to Fusarium oxysporim f.sp. Cubense Tropical Race 4 (Foc TR4), towards Understanding the Genetic Base of Host- Pathogen Interactions” through funding from the CGIAR Program for Roots,Tubers and Bananas (RTB). Contributions were made by the University of Philippines Los Banos, Lapanday Food Corporation and the Bureau of Plant Industry, all based in the Philippines.